Procedural Volume and Outcomes After Septal Reduction Therapies in Hypertrophic Obstructive Cardiomyopathy - Nirav Patel; Naman S. Shetty; Mokshad Gaonkar; Abdulla Shahid; Girija P. Divekar; Akhil Pampana; Nehal Vekariya; Peng Li; Mustafa I. Ahmed; Garima Arora; Pankaj Arora (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Septal myectomy and alcohol septal ablation (ASA) are septal reduction therapies for patients with symptomatic obstructive hypertrophic cardiomyopathy. Operator and hospital volume may influence outcomes, but contemporary data on this relationship are limited. Methods and Results This retrospective cohort study used data from the Vizient Clinical Data Base (2016–2022). Patients with undergoing septal myectomy and ASA were identified using International Classification of Diseases, Tenth Revision, Clinical Modification (ICD‐10‐CM) codes and stratified into low‐, medium‐, and high‐volume groups based on annualized operator and hospital volumes. The outcomes were 30‐day in‐hospital mortality and 90‐day readmission, analyzed using multivariable adjusted logistic and Cox models. Among 5725 patients with hypertrophic cardiomyopathy (3990 septal myectomy; 1735 ASA), most operators and hospitals performed <10 procedures annually. For septal myectomy, low‐volume operators were associated with higher odds of 30‐day mortality (adjusted odds ratio [aOR], 1.86 [95% CI, 1.11–3.15]) and greater risk for 90‐day readmission (aOR, 1.51 [95% CI, 1.22–1.88]), and medium‐volume operators had higher odds of 30‐day mortality (aOR, 1.93 [95% CI, 1.05–3.55]). Medium‐volume hospitals had higher 30‐day mortality (aOR, 2.29 [95% CI, 1.32–3.99]), with low‐volume hospitals showing greater risk for 90‐day readmission (aOR, 1.60 [95% CI, 1.14–2.23]). For ASA, low‐ and medium‐volume operators had increased 30‐day mortality (aOR, 2.99 [95% CI, 1.15–7.75] and aOR, 3.86 [95% CI, 1.30–11.46]), but the risk of 90‐day readmission was similar. Hospital volumes did not significantly impact outcomes for ASA. Conclusions Low operator and hospital volumes were associated with worse outcomes for septal reduction therapies, emphasizing the need to refer patients with hypertrophic cardiomyopathy to high‐volume centers with experienced operators.